Irisin Levels Related to Glycosylated Hemoglobin in Type 2 Diabetic Obese Women - Alkhader , Raghd A. Y.; Ali , Khitam Abdul Wahab; Al-Kharasani, Abbas Mahdi Rahmah (Iraqi Journal of Science, 2020)
The aim of the preset study is to explain the role of irisin hormone levels in type-2 obese diabetic women and compare these levels with those in obese nondiabetic women. In addition, we investigated the relation of irisin levels with those of glycated hemoglobin (HbA1c) and body mass index (BMI) in the patients.Eighty eight subjects were included in this study, including 44 type-2 Iraqi obese diabetic women as a patients group, and 44 obese nondiabetic women as a control group. Serum irisin was measured by Enzyme-linked Immune-Sorbent assay (ELISA), while determination of glycosylated Hemoglobin was carried out by The SD A1c CareTM system. Diabetic type-2 obese women showed a highly significant decrease in the levels of serum irisin when compared to levels in obese non-diabetic women, while no significant changes were observed in the meanÂ±SD values when comparing age and duration of DM. In the patients, a negative correlation was found between serum irisin and HbA1c while no significant correlation was recorded between the hormone levels and BMI.